Implementation of the Global Plan of Action in Europe -conservation and sustainable utilization of plant genetic resources for food and agriculture: Proceedings of the European Symposium, 30 June-3 July 1998, Braunschweig, Germany - Gass, T.; Frese, L.; Begemann, F.; Lipman, E.; International Plant Genetic Resources Institute; European Cooperative Programme for Plant Genetic Resources; Food and Agriculture Organization of the United Nations (1999)
The Global Plan of Action on Plant Genetic Resources for Food and Agriculture (GPA) adopted in Leipzig, Germany in June 1996, is probably the single most important milestone in achieving a global multilateral system for plant genetic resources. Throughout the preparatory process leading to the Leipzig Conference, government agencies, NGOs, international organizations and scientific institutions have invested much effort in making the GPA realistic and useful. In implementing the GPA, the European region has to face numerous challenges. The large number of very diverse countries, their high level of interdependence, and the heterogeneity of national needs and resources make Europe “a world in a region”, a laboratory in which the lessons that are being learned are likely to be relevant for the rest of the world community. The European Symposium on PGRFA held in June 1998 in Braunschweig, Germany, was intended to be a forum for the exchange of experiences and ideas and an occasion to take stock of the implementation of the GPA at the national and regional levels. Reading these proceedings, we will no doubt agree that these goals were successfully reached. Initiatives such as the one taken here by European countries are essential if, as an international community, we want to advance towards the goals that we have set in Leipzig and give substance to the policy framework which is currently under negotiation.